2022
DOI: 10.1186/s12967-022-03630-1
|View full text |Cite
|
Sign up to set email alerts
|

System analysis based on the cuproptosis-related genes identifies LIPT1 as a novel therapy target for liver hepatocellular carcinoma

Abstract: Background Liver hepatocellular carcinoma (LIHC) ranks sixth among the most common types of cancer with a high mortality rate. Cuproptosis is a newly discovered type of cell death in tumor, which is characterized by accumulation of intracellular copper leading to the aggregation of mitochondrial lipoproteins and destabilization of proteins. Thus, understanding the exact effects of cuproptosis-related genes in LIHC and determining their prognosticvalue is critical. However, the prognostic model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 96 publications
1
50
0
Order By: Relevance
“…Lipoyltransferase 1, encoded by LIPT1, is a vital enzyme that transfers lipoate to the E2 subunits of the 2-ketoacid dehydrogenase complexes, and the deficiency of it had already been confirmed to suppress TCA cycle metabolism (Solmonson et al, 2022). Studies have shown that LIPT1 is closely linked to a favorable outcome in patients with urothelial cancer, hepatocellular carcinoma, and melanoma (Chen et al, 2021;Lv et al, 2022;Yan et al, 2022). In this study, we found that LIPT1 was upregulated in PCa, but not correlated with the BCR.…”
Section: Discussionmentioning
confidence: 56%
“…Lipoyltransferase 1, encoded by LIPT1, is a vital enzyme that transfers lipoate to the E2 subunits of the 2-ketoacid dehydrogenase complexes, and the deficiency of it had already been confirmed to suppress TCA cycle metabolism (Solmonson et al, 2022). Studies have shown that LIPT1 is closely linked to a favorable outcome in patients with urothelial cancer, hepatocellular carcinoma, and melanoma (Chen et al, 2021;Lv et al, 2022;Yan et al, 2022). In this study, we found that LIPT1 was upregulated in PCa, but not correlated with the BCR.…”
Section: Discussionmentioning
confidence: 56%
“… 51 A recent study showed that the expression of LIPT1 not only effectively predicts the prognosis of patients with HCC but also may become a therapeutic target for HCC. 52 DLAT, a key gene that catalyzes the conversion of pyruvate to acetyl CoA, can enhance ATP production and promote tumor cell proliferation. 53 CDKN2A, encoding the cyclin inhibitor p16, binds to cyclin and cyclin-dependent kinases 4 and 6 to inhibit proliferation in normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Copper, a cofactor for various enzymes, is an essential micronutrient required for normal cell function, and the cuproptosis is related to various cancer progressions, such as HCC [ 19 , 20 ]. Recent studies have determined that serum and liver copper are related to NAFLD, but the specific mechanism is still unclear [ 21 ].…”
Section: Discussionmentioning
confidence: 99%